Low-dose computed tomography for the diagnosis of pneumonia in elderly patients: a prospective, interventional cohort study. Issue 5 (31st May 2018) - Prendki, Virginie; Scheffler, Max; Huttner, Benedikt; Garin, Nicolas; Herrmann, François; Janssens, Jean-Paul; Marti, Christophe; Carballo, Sebastian; Roux, Xavier; Serratrice, Christine; Serratrice, Jacques; Agoritsas, Thomas; et al.
The diagnosis of pneumonia is challenging. Our objective was to assess whether low-dose computed tomography (LDCT) modified the probability of diagnosing pneumonia in elderly patients. We prospectively included patients aged over 65 years with a suspicion of pneumonia treated with antimicrobial therapy (AT). All patients had a chest radiograph and LDCT within 72 h of inclusion. The treating clinician assessed the probability of pneumonia before and after the LDCT scan using a Likert scale. An adjudication committee retrospectively rated the probability of pneumonia and was considered as the reference for diagnosis. The main outcome was the difference in the clinician's pneumonia probability estimates before and after LDCT and the proportion of modified diagnoses which matched the reference diagnosis (the net reclassification improvement (NRI)). A total of 200 patients with a median age of 84 years were included. After LDCT, the estimated probability of pneumonia changed in 90 patients (45%), of which 60 (30%) were downgraded and 30 (15%) were upgraded. The NRI was 8% (NRI event (−6%) + NRI non-event (14%)). LDCT modified the estimated probability of pneumonia in a substantial proportion of patients. It mostly helped to exclude a diagnosis of pneumonia and hence to reduce unnecessary AT. Low-dose CT modified the estimated probability of pneumonia in a substantial proportion (45%) of elderly patients http://ow.ly/V1ha30jvOMk